2015
DOI: 10.1111/1365-2745.12494
|View full text |Cite
|
Sign up to set email alerts
|

Leaf colour polymorphisms: a balance between plant defence and photosynthesis

Abstract: Summary 1.Whether plants use leaf colour to deter herbivores remains controversial. The warning signal hypothesis predicts that red pigmentation is adaptive by reducing herbivory; plants with predominantly red foliage should have higher fitness than those with green leaves. Despite many discussions, this prediction has rarely been tested, and alternative, non-exclusive hypotheses cannot be ruled out. 2.We have exploited leaf colour polymorphism in Pseudowintera colorata to test the warning signal hypothesis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 58 publications
0
33
0
5
Order By: Relevance
“…A more recent study by Chen and Huang, 24 suggests that through phylogenetic analysis, young red leaves have less mechanical protection (in the form of enhanced cuticle, epidermis and trichomes) compared to the green young leaves. Menzies et al 25 demonstrated that the red leaves of the Pseudowintera colorata, has a higher concentration of antifeedant chemical components, incurring less herbivory damage and reduced leaf eating infestation from insects. Hughes and Lev-Yadun 26 discusses the numerous potential ecological and physiological of having red colored leaf margin.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study by Chen and Huang, 24 suggests that through phylogenetic analysis, young red leaves have less mechanical protection (in the form of enhanced cuticle, epidermis and trichomes) compared to the green young leaves. Menzies et al 25 demonstrated that the red leaves of the Pseudowintera colorata, has a higher concentration of antifeedant chemical components, incurring less herbivory damage and reduced leaf eating infestation from insects. Hughes and Lev-Yadun 26 discusses the numerous potential ecological and physiological of having red colored leaf margin.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the chemical structure of anthocyanins and their histological localization, different protective functions have been hypothesized even though, concerning plant protection against abiotic stress, photoprotection from high light and UV-B (Agati et al, 2007;Tattini et al, 2014) and ROS scavenging ability are the most widely postulated as stress reliever (Gould et al, 2002;Kytridis and Manetas, 2006). On the other hand, defence against herbivores and attraction of pollinators (or preys in carnivorous plants) are the most proposed functions for anthocyanins in terms of relationships with biotic factors (Gould et al, 2009;Hughes and Lev-Yadun, 2015;Menzies et al, 2015). Despite the impossibility to find an universal role for these flavonoids, what in many cases anthocyanic species have in common is the up-regulation of the biosynthesis of those compounds as a cross response to different environmental constrains such as high light, UV-B waveband, drought, high temperatures, ozone, bacterial and fungal infections, wounding, herbivores, herbicides and many other pollutants (i.e., heavy metals) (for review see Landi et al, 2015).…”
Section: The Key Role Of Phenols In Terrestrial Plants Evolutionmentioning
confidence: 99%
“…Variation in floral anthocyanin content or pattering may be under selection by pollinators (Ortiz-Barrientos, 2013;Sletvold, Trunschke, Smit, Verbeek, & Ågren, 2016) or nonpollinators alike (Narbona, Wang, Ortiz, Arista, & Imbert, 2017;Strauss & Cacho, 2013;Strauss & Whittall, 2006). Similarly, the accumulation of anthocyanins in vegetative organs or tissues such as leaves, stems, or pedicels is also influenced by direct or indirect selection of biotic and abiotic factors (Cooney, Schaefer, Logan, Cox, & Gould, 2015;Gould et al, 2010;Menzies et al, 2016). In order to estimate the fitness consequences of such anthocyanin variation (e.g., Del Valle et al, 2015;Sletvold et al, 2016), one must employ an efficient, noninvasive method such as digital photography.…”
Section: Discussionmentioning
confidence: 99%
“…In reproductive organs, anthocyanins help attract pollinators or seed dispersers, whereas in vegetative organs, they provide protection against environmental stressors such as UV-B radiation, excess light, cold, drought, salinity, pathogens, and/or herbivores (Landi et al, 2015;Lee & Gould, 2002;Schaefer & Ruxton, 2011). Variation in floral and vegetative anthocyanin concentrations within and among populations is common and often adaptive (e.g., Del Valle, Buide, Casimiro-Soriguer, Whittall, & Narbona, 2015;Menzies et al, 2016). Therefore, it is undeniable that the quantification of anthocyanins has become fundamental in understanding many aspects of plant evolutionary ecology (Ortiz-Barrientos, 2013;Sobel & Streisfeld, 2013).…”
Section: Introductionmentioning
confidence: 99%